Unusual size, topography, and surgical resolution of an acquired fibrokeratoma - Leandro Fonseca Noriega; Nilton Gioia Di Chiacchio; Nilton Di Chiacchio; Andreza Ventura (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Acquired fibrokeratoma is a rare benign skin tumor that usually manifests as a slow-growing solitary nodular lesion of the digits. We report a case of plantar acquired fibrokeratoma evidencing its atypical size and topography, in addition to the treatment with simple surgical excision followed by healing by second intention. Nondigital fibrokeratomas may occur in 18% of cases and rarely affect the palmoplantar region. These lesions are usually asymptomatic and show ≥ 3cm in size at the time of diagnosis due to delayed diagnosis. Complete surgical excision is the treatment of choice, which is usually curative. In general, primary closure is chosen; however healing by second intention becomes an option in regions of difficult approach.